The Effect of Active Range of Motion (ROM) Exercises on Blood Pressure Changes in Older Adults with Hypertension at Tanjung Rejo Community Health Center, Percut Sei Tuan, Medan, in 2025 - Zuidah Zuidah; Indah Wati; Srimislaini Saragih (Cattleya Darmaya Fortuna, 2026)
Hypertension is one of the leading non-communicable diseases worldwide and a major contributor to cardiovascular morbidity and mortality. Inadequate physical activity is a modifiable risk factor associated with poor blood pressure control among older adults with hypertension. Active Range of Motion (ROM) exercises have been proposed as a simple, safe, and low-cost non-pharmacological intervention to improve cardiovascular function and reduce blood pressure. This study aimed to determine the effect of Active ROM exercises on blood pressure among older adults with hypertension. A quasi-experimental study with a one-group pretest–posttest design was conducted at the Tanjung Rejo Community Health Center, Percut Sei Tuan, Medan, Indonesia. Twenty-five older adults with Stage I hypertension were recruited using purposive sampling. Blood pressure was measured before and after participants performed Active ROM exercises for three consecutive days. Descriptive statistics were used to summarize participant characteristics and blood pressure measurements, while inferential analysis was performed to evaluate changes in blood pressure before and after the intervention. Statistical significance was established at p < 0.05. The mean blood pressure decreased from 154/93 mmHg before the intervention to 137/90 mmHg after the Active ROM exercise program. The proportion of participants with Stage II hypertension decreased substantially, while the number of participants with normal blood pressure increased following the intervention. Statistical analysis demonstrated a significant reduction in blood pressure after Active ROM exercises (p = 0.000, p < 0.05). Active Range of Motion (ROM) exercises significantly reduced blood pressure among older adults with hypertension. These findings suggest that Active ROM exercises represent a practical, safe, and effective non-pharmacological intervention that can be incorporated into routine hypertension management programs in primary healthcare settings.